Use of artificial intelligence in fire safety in solar photovoltaic systems (Research, Society and Development, 2023)
Photovoltaic solar energy, especially in the form of Distributed Generation (DG), plays an essential role in the global energy matrix, including the Brazilian scenario. This article aims to analyze the application of Artificial Intelligence (AI) in fire safety in photovoltaic solar systems, focusing on improving and optimizing prevention, detection and response processes to fire-related incidents. Therefore, it becomes essential to implement comprehensive measures, especially intelligent arc detection and rapid shutdown technologies, in order to improve the safety and management of PV plants, whether in residential, commercial and industrial installations or even in solar farms. As a methodology, it adopts a descriptive approach and case study, of a qualitative nature, as well as bibliographical sources in books, articles and online journals, seeking to understand the application of AI in the safety of photovoltaic solar systems, as well as case analysis. specifications that exemplify the effectiveness of AI in preventing and responding to fire incidents in solar installations. Among the results, we seek to demonstrate the contributions of AI in a significant way to maximize safety and reliability for users of solar PV systems, protecting lives and properties. It is concluded that the application of AI in this context contributes not only to the protection of users and their properties, but also to the ongoing sustainability and reliability of solar PV power generation. Therefore, its use must be encouraged and regulated in accordance with current safety standards.